Taṭwīr Ta`līm Mahārah al-Kalām Bi Ṭarīqah IEQIE `Alā Asās Communicative Approach Wa Permissive Approach Laday aṭ-Ṭālibāt (Dirāsah al-Baḥṣ Wa Taṭwīr Bi MTsN 2 Aceh Timur): (MTsN 2 Aceh Timur دراسة البحث والتطوير بـ) لدى الطالبات Permissive Approach و Communicative Approach على أساس IEQIE تطوير تعليم مهارة الكلام بطريقة - Zahara, Alfi; Azwir, Azwir (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2023)
Speaking skills are students' ability to achieve meaning through words about students' ideas and feelings. As for teaching Arabic is not an easy thing, the teacher needs the right method so that students can understand it easily. This study aims to determine the steps of learning speaking skills using the IEQIE method based on the Communicative Approach and Permissive Approach and to determine the effectiveness of the IEQIE method based on the Communicative Approach and Permissive Approach. To collect data, the researcher validated the feasibility of the questions to be used, the pre-test and post-test, as well as a questionnaire for students. The population in this study were all students for the 2022-2023 school year at MTsN 2 Aceh Timur, totaling 328 students spread over 20 classes. The researcher took as a sample, namely students in grades 2(a) and 2(b), which totaled 51 students. The results of research on the development of learning speaking skills using the IEQIE method based on the Communicative Approach and the Permissive Approach are effective with the T-test. On the Arabic speaking test in the form of a conversation, the result is (7.697) and the test on students' ability to answer questions related to the material being discussed is obtained (17.287), and the significance level (Sig.) 0.05 > 000). The student response was good in teaching speaking skills by developing the IEQIE method, getting a result of 88%, meaning very good.